REVOLUSI PEMERINTAHAN, SUDAHKAH BEREVOLUSI? KOLOKASI ADJEKTIVA KATA “INDONESIA” DALAM COCA DAN COHA PADA PERIODE PEMERINTAHAN ORDE LAMA, ORDE BARU DAN ERA REFORMASI - Almira Fidela Artha (ETNOLINGUAL, 2018)
Historically, Indonesia's system of government is divided into three periods, namely The old order, The new order and Reformation. Every government order has a different and changing image of the nation. This change can be analyzed by looking at the collocation of adjectives attached to the word "Indonesia" in the corpus of COCA (Corpus of Contemporary American English) and COHA (Corpus of Historical American English). The focus of this study is the collocation differences and similarities of the word "Indonesia" in three dimensions of time, namely The old order, The new order and Reformation. By using discourse analysis from Djik (1997), it is expected that the image of Indonesian nation in the eyes of the world represented by America in three periods of government can be seen. The results of this study indicated that the collocation of adjectival adjectives which follow the word "Indonesia" changed every period of government and the turn of this much backed by the context of the situation or historical record that occurred at each period.